Pengaruh Budaya Organisasi Dan Kepemimpinan Transformasional Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Mediasi Pada PT. Sasa Inti Gending - rizaldi, ade; Safrizal, Helmi Buyung Aulia (Jurnal Kajian Ilmu Manajemen (JKIM), 2025)
The purpose of this research is to ascertain how corporate culture and transformational leadership style affect worker motivation and performance enhancement. A proportionate stratified random selection technique was used to select 93 respondents from among the 1,200 employees of PT. Sasa Inti Gending, the study's population. A 5-point Likert scale questionnaire was used to collect the data, and SmartPLS software was used to analyze the results using the Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS). According to the study's findings, transformational leadership and a favorable corporate culture significantly boost workers' motivation for their jobs. Additionally, work motivation plays a mediating role in the interaction between organizational culture and transformational leadership on employee performance and has a major impact on enhancing employee performance. Strategic implications for human resource management are provided by this study, particularly with regard to initiatives to enhance employee performance through the development of optimal work motivation, the implementation of an inspirational leadership style, and the building of organizational culture.